PF-32 Radiography Assessment of Femoral Muscle and Bone Density in Rats as Response to Biodegradable Iron (Fe) Porous Implants - Arlita Sariningrum; Mokhamad Fakhrul Ulum; Sri Estuningsih; Deni Noviana (Hemera Zoa, 2018)
Iron (Fe) is considered as one group of metals that can be used as degradable metal implants (Schinhammer et al. 2010). Previous implantation studies have used porous Fe which purposes to increase the rate of degradation (Daud and Hermawan 2013). Changes in the condition of metal implants due to degradation and peri-implant muscle tissue reactions in the body can be observed using radiographic modality (Noviana et al. 2013). The aim of this study was to assess the radiographic density of implants, peri-implants and peri-implants-muscle as a response to Fe porous implants on the femur of the rats.